2012
DOI: 10.1179/2042618612y.0000000002
|View full text |Cite
|
Sign up to set email alerts
|

Lumbopelvic manipulation in patients with patellofemoral pain syndrome

Abstract: The previously identified CPR was not able to be replicated and no clinically meaningful changes in range of motion, strength, or function were apparent. Future research should focus on a comprehensive impairment-based treatment approach in patients with patellofemoral pain syndrome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
21
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 63 publications
0
21
0
Order By: Relevance
“…Most pain squatting (mean 2.27, 95 % CI 1.57-3.28), greater patella glide (mean 1.59, 95 % CI 1.18-2.26), less stiffness (mean 0.43, 95 % CI 0.3-0.61) and fewer episodes of giving way (mean 0.65, 95 % CI 0.49-0.86) and clicking (mean 0.64, 95 % CI 0.47-0.88) were shown to be significant predictors of lumbopelvic manipulation success [21]; however, these findings were not replicated in a follow-up study using the methodological design [41].…”
Section: Kneementioning
confidence: 63%
See 1 more Smart Citation
“…Most pain squatting (mean 2.27, 95 % CI 1.57-3.28), greater patella glide (mean 1.59, 95 % CI 1.18-2.26), less stiffness (mean 0.43, 95 % CI 0.3-0.61) and fewer episodes of giving way (mean 0.65, 95 % CI 0.49-0.86) and clicking (mean 0.64, 95 % CI 0.47-0.88) were shown to be significant predictors of lumbopelvic manipulation success [21]; however, these findings were not replicated in a follow-up study using the methodological design [41].…”
Section: Kneementioning
confidence: 63%
“…Furthermore, a subsequent single-arm cohort study reported none of the initially identified predictors for lumbopelvic manipulation success were predictive when the same methods were repeated [41]. Further good-quality case-control studies, exploring the effectiveness of this intervention within PFP populations should be sought prior to attempting to identify subgroups of individuals who may benefit.…”
Section: Kneementioning
confidence: 91%
“…Even if a lower threshold of five participants in the limiting sample size for each potential predictor is used,29 this was still the only study that had adequate statistical power. An issue with potential reporting bias was identified with only 428 30–32 of the 12 studies administered outcome measures in a blinded fashion and in only 3 studies were the examining28 30 33 or treating30 32 34 clinicians blind to the outcome measures (table 3). …”
Section: Resultsmentioning
confidence: 99%
“…1 It has a higher incidence in women than in men, 2 especially between 15 and 30 years old, [3][4][5][6][7] and it represents 25% to 40% of all treated disorders in sports medicine. [8][9][10][11][12][13] Patellofemoral pain syndrome often is referred to as patellofemoral chondritis, chondropathy, chondromalacia, anterior knee pain, patellar subluxation, patellar dislocation, or external overpressure syndrome. However, Patellofemoral pain syndrome is different from the patellar chondromalacia.…”
Section: Introductionmentioning
confidence: 99%